Seasonal dynamics and genetic diversity of human adenoviruses in patients with acute respiratory infection in Thailand, 2024 - Jiratchaya Puenpa; Lita Tantipraphat; Ratchadawan Aeemjinda; Preeyaporn Vichaiwattana; Sumeth Korkong; Yong Poovorawan (PLoS ONE, 2025)
Human adenoviruses (HAdVs) are a significant cause of acute respiratory infections (ARIs), particularly in pediatric populations. Continuous molecular surveillance is essential to understand their epidemiology, genetic diversity, and seasonal dynamics. In 2024, a surveillance study was conducted in Bangkok, Thailand, involving 8,130 nasopharyngeal swabs collected from ARI patients. HAdV was detected in 5.3% (429/8,130) of ARI cases, with peak weekly positivity reaching 17.7% during weeks 10–12 (March). These HAdV-positive samples were subsequently genotyped through partial hexon gene sequencing and phylogenetic analysis using the maximum likelihood method. HAdV-B3 was the predominant genotype (70.7%), followed by HAdV-C2 (11.6%) and HAdV-C1 (10.4%). Genotype diversity increased toward the end of the year, with the emergence of HAdV-B7, C5, and C6. The majority of cases occurred in children aged 0–9 years, with HAdV-B3 dominating across all pediatric groups. Phylogenetic analysis revealed close genetic relationships between Thai strains and reference strains from China, Japan, the USA, and Europe, indicating both local circulation and international linkages. Despite the detection of HAdV-B7, no severe outcomes were reported in this cohort. This study also reports potential relevant sites under episodic positive selection in the hexon gene, suggesting adaptive evolution at specific codon positions. This study provides updated insight into the molecular epidemiology of HAdV in Thailand. The findings highlight seasonal and age-specific patterns in genotype distribution and underscore the importance of continued genomic surveillance to detect emerging variants and guide public health responses.